Characteristics Analysisof Transient Process Electromagnetic Torque of Generator with Stator Winding Short Circuit Fault - CHEN Chao; ZHAO Hong-sen; CHEN Xiao-yuan; GE Bao-jun (Journal of Harbin University of Science and Technology)
In order to study the change characteristics of electromagnetic torque in the transient process of stator internal short circuit fault, based on virtual work principle in dynamic, the electromagnetic torque of transient process after stator winding interturn short circuit fault in synchronous generator is analyzed theoretically. The air gap magneto motive forces variation characteristics of the generator before and after short circuit fault in stator winding are studied, while considering the impact of vibration eccentricity. The magnitudes and frequency variation characteristics of the electromagnetic torque component of each frequency after short circuit fault are obtained. Then a dynamic simulation experiment model is built. The electromagnetic torque data of the 30kVA synchronous generator with different stator winding interturn short circuit faults is tested.After that, these data are analyzed with Discrete Fast Fourier Transform technique, and the test results verify the theoretical analysis conclusion. The research results provide a theoretical basis for the internal fault diagnosis technology based on the electromagnetic torque.